New geophysical evidences of the presence of a buried caldera in Laguna Pozuelos, Northern Puna - Prezzi, C.B. (2010)
In the southern border of Laguna de Pozuelos Basin, the Pan de Azúcar volcanic complex crops out. It consists of several dacitic volcanic dome centers of ~ 12 Ma. Previous interpretation of seismic lines and a detailed ground magnetic survey indicated the presence of buried intrusive bodies. The determination of the existence of buried bodies has two major implications: 1) these volcanic complexes are closely associated with ore deposits (as part of the Bolivian tin ore polymetallic belt); and 2) the existence of a large ancient caldera (~12 Ma) beneath the central and southern part of the Laguna de Pozuelos Basin, covered by the infilling sediments was previously suggested. The volcanic complexes would represent the final stages of such a calderic magmatic system. In order to confirm the existence of other buried intrusives and/or a buried caldera system, detailed ground magnetic and gravity surveys were carried out. The magnetic map is dominated by positive and negative anomalies in the southern sector of the basin, associated with the dacitic domes. The residual Bouguer anomaly presents a semicircular pattern, having only positive values. We applied the curvature technique to analyse the magnetic and gravity signals and used Euler deconvolution to estimate the depth to the sources. Our results would support the hypothesis of a large caldera buried beneath the Laguna de Pozuelos Basin. The identification of such a large Middle Miocene caldera would bring new insight into the magmatic evolution of the northern Puna.